A Neber approach for the synthesis of spiro-fused 2H-azirine-pyrazolone. Issue 6 (19th January 2016) - Yue, Deng-Feng; Zhao, Jian-Qiang; Wang, Zhen-Hua; Zhang, Xiao-Mei; Xu, Xiao-Ying; Yuan, Wei-Cheng
Abstract : A base-mediated Neber reaction of enaminopyrazolones with sulfonyl chlorides was developed and various spiro-fused 2 H -azirine-pyrazolones were obtained in good yield. Abstract : A base-mediated Neber reaction of enaminopyrazolones, which are the tautomers of 4-acyloxime-2-pyrazolin-5-ones, with sulfonyl chlorides was achieved. With this developed approach, a range of spiro-fused 2 H -azirine-pyrazolones were obtained in good yields under mild conditions. A preliminary trial of a catalytic asymmetric version of the Neber reaction was conducted and gave promising enantioselectivity.